Recent advances in energy usage and environmental degradation: Does quality institutions matter? A worldwide evidence. (November 2021) - Khan, Hayat; Weili, Liu; Khan, Itbar; Oanh, Le thi Kim
Abstract: Environmental quality has become an important concern and topic of research recently in preceding studies. Several factors includes in environmental degradation such as the usage of energy from fossil fuels, releasing of high carbon dioxide, sulfur dioxide and air pollution, greenhouse effect and so on. Mixed conclusion has been achieved by studying several factors related to environmental quality in the prevailing literature. The current study therefore explore the relationship of environmental factors by taking into consideration the role of institutional quality and technological progress in the global panel of 188 countries. Panel data for the period of 2002 to 2018 is used and have applied both static and dynamic models includes OLS, fixed effect, GMM and system GMM models. The findings indicate that the use of renewable energy form renewable sources instead of energy use from fossil fuels has been found beneficial for environment as non-renewable energy consumption increase carbon emission in our results. Financial development positively while FDI have negative impact on carbon emission. Technological progress exerts positive impact where most of institutional quality variables have been found significant for carbon emission. The findings suggest policy makers on further polices by using renewable energy sources and suggest focusing on technological innovation and funding renewable energy projects through financial institutions to achieve higher quality of environment.